PERSEPSI GURU TENTANG TANTANGAN MENGAJARKAN MATERI IPAS WARNA-WARNI KEHIDUPAN DALAM EKOSISTEM DI KELAS V SD - Ria Annisa; Reva Atika; Tri Yunitasari; M. Iqbal Arrosyad (CV. ADIBA AISHA AMIRA, 2025)
Learning the colorful life science material in ecosystems in fifth grade elementary school faces various obstacles related to student understanding. This study aims to describe teachers' perceptions regarding the challenges in teaching this material at Muhammadiyah Elementary School Pangkalpinang. This study uses a qualitative approach with a focus on teachers' experiences in the learning process. The subjects of this study were fifth grade teachers who teach ecosystems. The study was conducted on October 21, 2025, at Muhammadiyah Elementary School Pangkalpinang. Data collection techniques included in-depth interviews to determine teachers' perceptions, observations to directly observe the learning process, and documentation as supporting primary data. The results showed that teachers assessed the level of difficulty of the material based on students' responses during learning and evaluation results that indicated parts of the concept that had not been understood. The teacher explained that the concept that needed frequent repetition was the relationship between biotic and abiotic components because some students still had difficulty understanding the relationship. The material that was considered quite difficult was the interaction of living things and energy flow, so the teacher addressed this by providing real examples from the school environment and displaying supporting visuals. In the teaching process, the teacher used Canva's interactive PPT which was considered easier to understand because of its attractive and clear appearance. Lectures, presentations, and educational games are also used alongside the TGT model to increase student engagement. Teachers assess the sufficiency of learning time, and if insufficient, assign students additional assignments to deepen the material.